Recentes transformações nos processos de urbanização: estudo de caso do município de Aracruz/ES - Cabral Junior, Roberto (2019)
The work seeks to reflect on new movements in the processes of urbanization of the contemporary city, having as empirical study the municipality of Aracruz-ES. Analyzing the recent changes in urbanization processes, it is intended to understand their impact on municipal management and its socio-spatial impacts. At first, Aracruz underwent an intense process of urbanization and demographic growth, generated by the establishment of the Aracruz Florestal Industry, later Aracruz Celulose Industry (1970 to 1980 decade), provoking intense socio-environmental conflicts. More recently, there is a second cycle of intense urbanization in the municipality, which is linked to the process of productive restructuring/financialization of the globalized economy, plus a 3rd cycle of investments for large projects in Espírito Santo, headed by the oil and gas sector Natural. Since then, new patterns of urbanization, with different actors (such as public companies) have modified the urban setting and municipal management. The intensive approval of real estate developments in the last 15 years has expanded the urban network in a vertiginous way, supposedly justified by the strong economic dynamics of the municipality and its population growth. This scenario leads us to question: what are the effects of the influence of the economic-financial system on the instruments of urban legislation and the territorial configuration of contemporary cities, and of Aracruz? When the question is asked, it is investigated in two perspectives: A) the current records of the socioeconomic and urban landmarks that act in the production of the territory of Aracruz; and B] to the effects produced by the real estate market in the urbanization of new areas in the municipality of Aracruz-ES and its socio spatial impacts.